The Efficacy of Venlafaxine, Flunarizine, and Valproic Acid in the Prophylaxis of Vestibular Migraine - Liu, Fenye; Ma, Tianbao; Che, Xiaolin; Wang, Qirong; Yu, Shudong (Frontiers in Neurology, 2017)
Background: Different types of medications are currently used in vestibular migraine (VM) prophylaxis, although recommendations for use are generally based on expert opinion rather than on solid data from randomized trials. We evaluated the efficacy and safety of venlafaxine , flunarizine and valproic acid in a randomized comparison trial for VM prophylaxis. Methods: Subjects were randomly allocated to one of three groups (venlafaxine group, flunarizine group, and valproic acid group). To assess the efficacy of treatment on vertigo symptoms, the following parameters were assessed at baseline and 3 months after treatment: Dizziness Handicap Inventory (DHI) scores, number of vertiginous attacks in the previous month, and Vertigo Severity Score. Adverse events also were evaluated. Results: A decrease in DHI total scores was shown following treatment with all three medications, with no obvious differences between the groups. Treatment effects differed, however, in the DHI physical, functional, and emotional domains with only venlafaxine showing a decreased effect in all of three domains. Flunarizine and valproic acid showed an effect in only one DHI domain. Venlafaxine and flunarizine showed decreased VSS scores (p=0 and p=0.03, respectively). Although valproic acid had no obvious effect on VSS (p=0.27), decreased vertigo attack frequency was observed in this group (p=0). Venlafaxine also had an effect on vertigo attack frequency (p=0) but flunarizine had no obvious effect (p=0.06). No serious adverse events were reported in the three groups. Conclusions: Our data confirm the efficacy and safety of venlafaxine, flunarizine and valproic acid in the prophylaxis of VM, venlafaxine had an advantage in terms of emotional domains. Venlafaxine and valproic acid also was shown to be preferable to flunarizine in decreasing the number of vertiginous attacks, but valproic acid was shown to be less effective than venlafaxine and flunarizine to decrease vertigo severity.